Elastographic and echotextural characteristics of foetal lungs and liver during the final 5 days of intrauterine development in dogs - Rodrigues Simões, Ana Paula [UNESP]; Rossi Feliciano, Marcus Antonio [UNESP]; Maronezi, Marjury Cristina [UNESP]; Uscategui, Ricardo Andres Ramirez [UNESP]; Bartlewski, Pawel Mieczyslaw; de Almeida, Vivian Tavares [UNESP]; Oh, David; do Espírito Santo Silva, Paloma [UNESP]; da Silva, Liege Cristina Garcia; Russiano Vicente, Wilter Ricardo [UNESP] (Elsevier, 2018)
Objective was to evaluate the echotexture and characteristics during terminal development of canine foetal respiratory and hepatic systems through elastographic examinations. Fifteen pregnant bitches were evaluated by ultrasonography twice daily, from the 53rd gestational day until whelping, and images obtained from 120 to 0 h before parturition were analysed. Images of foetal lungs and liver were recorded and then used for computer-assisted analyses to determine quantitative attributes. Acoustic Radiation Force Impulse (ARFI) elastographic of internal organs were classified as 'soft’ (white areas) or ‘hard’ (dark areas) and quantitative analyses determined the mean shear wave velocities (SWV) of foetal lungs and liver. After delivery, canine neonates were clinically evaluated, and their health status was monitored weekly until 60 days post-partum. Sonographic parameters over time were compared by ANOVA and Pearson's correlations were used to determine associations between SWVs and echotextural variables. Foetal lungs and liver had a homogeneous echotexture and pulmonary parenchyma appeared hyperechoic when compared with that of the liver. Mean numerical pixel values (NPVs) of lungs decreased from 120 to 24 h and subsequently increased until parturition (P = 0.04). Lungs and liver mean (± SD) SWVs (0.98 ± 0.12 and 0.84 ± 0.11 m/s, respectively) didn't vary (P > 0.05) over time. Fluctuations in pulmonary NPVs indicated there was a pattern corresponding to structural and functional changes that occur during the terminal stage of pre-natal canine development and hence can be a useful diagnostic tool in veterinary. Foetal lung and liver SWVs were relatively consistent and there was no detectable changes during the pre-partum period for this variable or in echotexture.
Keywords: Canine; Development; Elastography; Foetal; Ultrasonography